Candolle was wrong, but finally right: Polygala ovata belongs to Hebecarpa (Polygalaceae) - Mota, Michelle; Barêa Pastore, José Floriano; Ferlay, Beijamin; Krasinski Caddah, Mayara (Phytotaxa, 2024)
A comprehensive review of the name Polygala ovata Poiret (1804), basionym of the widely used Asemeia ovata, revealed strong evidence to an alternative interpretation of this name as used by Pastore and Abbott in their Asemeia treatment in 2012. Issues arise from discrepancies between Poiret’s identification in specimens kept in P herbarium as P. ovata, and the original specimen of Nectoux from the Dominican Republican. De Candolle promoted the first attempted to resolve the application of Polygala ovata, however he had different approaches, when included this name in Prodromus, and later in the specimen identification as P. ovata. The present study reevaluates P. ovata identity based on original herbarium specimens, protologue information and original morphological description. The evidence found supports reclassifying P. ovata as a member of genus Hebecarpa instead, and therefore a new combination is proposed here, along with a morphological plate and taxonomic and distribution notes.